Comparing Total Cost of Ownership of Electric and Conventional Motorcycles in Indonesia - Sayyidah Maulidatul Afraah; Yuniaristanto Yuniaristanto; Wahyudi Sutopo; Muhammad Hisjam (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
The adoption of Electric Vehicles (EV) is one of the solutions to reduce emission problems. In Indonesia, the government targets 2.1 million Electric Motorcycles (EM) ownership in 2025. One of the keys to encouraging the EV Indonesian market is vehicle cost analysis, like Total Cost of Ownership (TCO). This study developed a TCO model to compare EM with Conventional Motorcycles (CM) in Indonesia. Data were collected from surveys and information from stakeholders. The proposed TCO model considered a battery replacement cost, which influenced the resale value of the vehicle. As a result, the TCO of EM had a more economical value than CM of 12% (IDR 3 million) on low mobility, 16% (IDR 4 million) on medium mobility, and 18% (IDR 5.5 million) on high mobility. In addition, several scenarios were also analyzed as a study to consider providing subsidies ownership motorcycles in Indonesia.